Ring Around the Moon : Mommy Goose Rhymes - Norris, Mike (Book collections on Project MUSE., 2019)
As this collection adeptly illustrates, nursery rhymes not only evoke innocence, discovery, and joy for children of all ages, but they also can educate and celebrate tradition. Ring Around the Moon features original rhyming poems in a time-honored Appalachian style that acknowledges the importance of the region and its rich heritage while introducing readers to the whimsical and enchanting world of Mommy Goose. With Kentucky-flavored language and subject matter, this volume brings together the words, art, and music of Appalachia. The poems present classic Appalachian subjects -- leaving the homeplace to find work, mountain folklore, country life versus city life -- and touch on a wide range of broader themes, such as bullying, gender roles, the power of language, and the power of kindness. This work is illustrated with more than 170 hand-painted carvings by renowned folk artist Minnie Adkins, often referred to as America's most important female wood carver. With sheet music for the original song "Ring Around the Moon" complementing the text, this multifaceted book entertains while capturing the spirit and expanding the range of traditional Appalachian nursery rhymes to reach a new generation of readers